Development of Micro Downwind Turbine Generator Having Soft Blades - Kouichi YOSHIDA; Xianwu LUO; Shuhong LIU; Hidenori EGUCHI; Michihiro NISHI (Journal of Fluid Science and Technology, 2011)
As there are frequent needs to install a micro wind turbine generator in a residential area, we have developed such a downwind-type turbine rotor having the following specifications: The rotor has the tip diameter of 1.5 m and three two-dimensional NACA0018 blades of 0.15 m chord whose material is light, soft and pliable foam plastic for perfect safety. From the wind tunnel test under the wind speed less than 14 m/s, it is clarified that the downwind turbine generator having soft blades has the low noise and the self-output-control characteristics, which are regarded as favorable for its actual operation. The latter feature is primarily attributed to bending and torsional elastic-deformation of the soft blade. The remarkable aerodynamic performances are summarized in this paper.